Les insectes du quartier portuaire romain de Saint-Lupien à Rezé/Ratiatum (Loire-Atlantique) : premiers résultats de l’étude archéoentomologique - David Pécréaux; Aurélia Borvon (Gallia)
The sediments bordering the quays of the Roman port district of Rezé/Ratiatum (Loire-Atlantique) proved to be favourable for an archaeo-entomological analysis. After extraction, the insect fragments provide information that complements the archaeological data. Many insects linked to the storage of foodstuffs, such as Sitophilus granarius, the wheat calandra or Bruchus sp., can be found. Wood-dwelling insects have also been identified, including Anobium cf. punctatum, the woodworm, and Scolytes such as Leperesinus varius. Finally, a large series of insects living in humid environments, particularly in decomposing plant matter, were identified, such as Staphylinidae accompanied by Scarabaeidae, taxa that are often coprophagous, such as Onthophagus vacca. The presence of these species therefore provides additional information on port activities and encourages further study of the entomological corpus.